Kinetic analyses on increase of bat head speed in baseball batting - Horiuchi, G.; Sakurai, S. (International Journal of Sport & Health Science, 2016)
The purpose of this study was to identify mechanisms to increase bat head speed in baseball batting, from the view-point of kinetics. The batting motion of ninety-nine amateur baseball players was recorded with a motion capture system, and the kinematics and kinetics of the bat were analyzed. The bat's rotational power increased with the torque exerted on the bat's grip. However, torque and rotational power declined just prior to impact. It can be interpreted that these declines arise from a decrease in torque exerted by the wrist's periarticular muscles as the bat's rotational velocity increases (muscle force-velocity relationship). On the contrary, the bat's translational power increased just prior to impact. Judging from the relationship between the force exerted on the bat's grip in the direction of the bat's long axis and the bat head speed, the bat's translational power seems to depend on the bat's grip velocity in the direction of the bat's long axis. It was revealed that the bat's energy, by the application of rotational and translational power at different times, contributes to an increase in bat head speed in baseball batting.